Pengaruh profitabilitas, likuiditas, ukuran perusahaan dan struktur modal terhadap nilai perusahaan industri dasar dan kimia - Suryadi Tampubolon; Jholant Bring Amelia Br Sinaga; Cindra Yesi Simatupang (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the effect of profitability, liquidity, firm size, and capital structure on firm value in basic and chemical industrial sector companies listed on the Indonesia Stock Exchange in 2016-2019. The number of samples is 27 companies in 4 years. Data were analyzed using a multiple linear regression model. The study found that simultaneously profitability, liquidity, firm size, and capital structure significantly affected firm value. However, partially, there is no significant effect of all the variables studied on firm value.